2018
DOI: 10.1021/acssuschemeng.7b03807
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Carbonized Design of 1D FeNi/C Nanofibers with Conductive Network to Optimize Electromagnetic Parameters and Absorption Abilities

Abstract: The optimized electromagnetic (EM) parameters are highly indispensable for outstanding microwave absorbers. Generally speaking, it is very necessary to suitably improve permittivity and permeability of the materials. The combination of magnetic/dielectric materials is a good choice. Herein, the irregular shaped FeNi/C composites were synthesized in N 2 atmosphere with unsatisfied EM parameters. To further optimize EM parameters and enhance microwave absorption abilities, constructing one-dimensional (1D) struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(56 citation statements)
references
References 68 publications
(86 reference statements)
0
56
0
Order By: Relevance
“…Regarding magnetic absorbers, 1D magnetic absorbing materials, such as FeNi/C nanofibers, [19] Fe/C nanofibers, [20] Fe nanowires, [21] Fe 3 O 4 @ carbon nanochain, [22] CoNi chains, [23] Ni chains, [24] and Co chains, [25,26] competitive EM wave absorption abilities and are lightweight and thin and have strong absorption because of the unique 1D structures, orientation polarization, and natural magnetic loss. [11,24,25] So far, it has been proven that the magnetic-field-induced synthesis is a process which mainly leads to the formation of magnetic metallic 1D nanostructures.…”
Section: Electromagnetic (Em) Wave Absorption Materials Have Attractementioning
confidence: 99%
“…Regarding magnetic absorbers, 1D magnetic absorbing materials, such as FeNi/C nanofibers, [19] Fe/C nanofibers, [20] Fe nanowires, [21] Fe 3 O 4 @ carbon nanochain, [22] CoNi chains, [23] Ni chains, [24] and Co chains, [25,26] competitive EM wave absorption abilities and are lightweight and thin and have strong absorption because of the unique 1D structures, orientation polarization, and natural magnetic loss. [11,24,25] So far, it has been proven that the magnetic-field-induced synthesis is a process which mainly leads to the formation of magnetic metallic 1D nanostructures.…”
Section: Electromagnetic (Em) Wave Absorption Materials Have Attractementioning
confidence: 99%
“…Based on their researches, we can discover that the microwave absorption performance closely depends on their design of one-dimensional nanostructures on carbon nanofibers. In principle, morphology change of carbon nanofibers could dramatically influence the transferring path of the electrons as well as the construction of the conductive network 19 . Accordingly, the permittivity and polarization process would be controlled in the range of testing frequency artificially.…”
Section: Introductionmentioning
confidence: 99%
“…86 Using polycarbosilane and ferric acetylacetonate as precursors, Hou et al 87 88 found that by tailoring the mass ratio of soft and hard phases, the reflection loss and the bandwidth could be optimized for wide-band microwave absorption. A similar material was applied by Xiang et al 89 91 Similarly, Bayat et al 92 found the electromagnetic shielding properties of electrospun Fe 3 O 4 /C nanofibers related to the carbonization temperature and the magnetite nanoparticle diameter. Absorption of thermal neutrons was investigated for PAN containing gadolinium, showing that the addition of this rare earth magnetic material significantly reduced the neutron transmissivity even through a thin shield.…”
Section: Absorption Of Microwave and Other Irradiationmentioning
confidence: 87%